PENGARUH GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE DAN LEVERAGE TERHADAP SUSTAINABLE GROWTH PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Annisa Devi Ainur Rohimah; Lilik Pirmaningsih (CV. Denasya Smart Publisher, 2025)
This study aims to analyze and empirically examine the role of green accounting, environmental performance, and leverage in driving sustainable growth among Food and Beverage companies listed on the Indonesia Stock Exchange during 2021–2023. Green accounting is operationalized through the extent of environmental cost disclosure, environmental performance is assessed using the PROPER score, and leverage is measured via the Debt to Equity Ratio. Sustainable growth serves as an indicator of long-term corporate development. The study population comprises 83 companies, from which a purposive sampling method was applied, resulting in a final sample of 66 companies. Using multiple linear regression analysis, the results reveal that sustainable growth is significantly influenced by all the independent variables investigated. These findings underscore the critical role of green accounting practices in promoting sustainable growth within the Food and Beverage sector.